Mapping the Functional Interaction of Sco1 and Cox2 in Cytochrome Oxidase Biogenesis - Rigby, Kevin (American Society for Biochemistry and Molecular Biology, 2008)
Sco1 is implicated in the copper metallation of the Cu(A) site in Cox2 of cytochrome oxidase. The structure of Sco1 in the metallated and apo-conformers revealed structural dynamics primarily in an exposed region designated loop 8. The structural dynamics of loop 8 in Sco1 suggests it may be an interface for interactions with Cox17, the Cu(I) donor and/or Cox2. A series of conserved residues in the sequence motif (217)KKYRVYF(223) on the leading edge of this loop are shown presently to be important for yeast Sco1 function. Cells harboring Y219D, R220D, V221D, and Y222D mutant Sco1 proteins failed to restore respiratory growth or cytochrome oxidase activity in sco1Δ cells. The mutant proteins are stably expressed and are competent to bind Cu(I) and Cu(II) normally. Specific Cu(I) transfer from Cox17 to the mutant apo-Sco1 proteins proceeds normally. In contrast, using two in vivo assays that permit monitoring of the transient Sco1-Cox2 interaction, the mutant Sco1 molecules appear compromised in a function with Cox2. The mutants failed to suppress the respiratory defect of cox17-1 cells unlike wild-type SCO1. In addition, the mutants failed to suppress the hydrogen peroxide sensitivity of sco1Δ cells. These studies implicate different surfaces on Sco1 for interaction or function with Cox17 and Cox2.